THE EFFECT OF ADAPTED MONOPOLY BOARD GAME TOWARDS ENGLISH LEARNING ACHIEVEMENT OF THE FOURTH GRADE STUDENTS OF PRIMARY SCHOOL IN BANJAR, BULELENG REGENCY, ACADEMIC YEAR 2015/2016 - ., I Putu Gede Hendra Raharja; ., Dra.Ni Made Ratminingsih, MA; ., Luh Diah Surya Adnyani, S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2016)
Penelitian ini bertujuan untuk menginvestigasi perbedaan prestasi belajar siswa antara siswa yang dibelajarkan dengan menggunakan Adapted Monopoly Board Game dan siswa yang dibelajarkan dengan menggunakan media pembelajaran konvensional di Banjar, Buleleng. Penelitian ini merupakan penelitian kuasi eksperimen yang menggunakan desain penelitian posttest only control group. Populasi dalam penelitian ini adalah seluruh siswa di Banjar, Buleleng yang berjumlah 182 siswa. Cluster random sampling digunakan sebagai teknik untuk menentukan sampel. Ada 2 kelompok sampel, SD N 1 Banjar ditetapkan sebagai kelompok kontrol dan SD N 9 Banjar ditetapkan sebagai kelompok eksperimen yang berjumlah 58 siswa. Data yang diperlukan dalam penelitian ini dikumpulkan dengan menggunakan instrumen penelitian berupa posttests. Data dianalisis secara deskriptif dan inferensial. Hasil dari analisis data menunjukan bahwa ada perbedaan yang signifikan diantara siswa yang dibelajarkan dengan menggunakan Adapted Monopoly Board Game dan siswa yang dibelajarkan menggunakan media pembelajaran konvensional. Rerata kelompok eksperimen (80.41) lebih tinggi daripada kelompok control (67.48). Hasil dari independent sample t-test menunjukan bahwa nilai t observed lebih tinggi daripada nilai t critical value (tobv = 6.544 > tcv = 2.003) pada taraf signifikansi 0.05 (α=0.05). Secara ringkas, Adapted Monopoly Board Game sebagai media pembelajaran memberikan efek yang signifikan terhadap prestasi belajar Bahasa Inggris siswa.Kata Kunci : Adapted Monopoly Board Game, Permainan Bahasa, Prestasi belajar Bahasa Inggris Siswa This study was aimed to investigate the significant difference in students’ English learning achievement between the students who were taught by using Adapted Monopoly Board Game and the students who were taught by using conventional teaching media in Banjar, Buleleng. This study was a quasi-experimental research using posttest only control group design. The population of this study was the fourth grade students in Banjar, Buleleng consisted of 182 students. To determine the sample, cluster random sampling technique was employed as a technique. There were 2 groups of sample, SD N 1 Banjar was assigned as control group, while SD N 9 Banjar was assigned as experimental group consisted of 58 students altogether. The required data for this study were collected by means of administering the research instrument in the form of posttests. The data was analysed descriptively and inferentially. The result of data analysis showed that that there was a significant difference between the students who were taught by using Adapted Monopoly Board Game and the students who were taught by using conventional teaching media. The mean of experimental group (80.41) was higher than control group (67.48). The result of independent sample t-test revealed that the value of t observed was higher than the t critical value (tobv = 6.544 > tcv = 2.003) at level significance 0.05 (α=0.05). In short, Adapted Monopoly Board Game as a teaching media gives significant effect to students’ English learning achievement at Banjar, Buleleng.keyword : Adapted Monopoly Board Game, English Learning Achievement, Language Game